The Populist Re-Politicization. Some Lessons from South America and Southern Europe - Padoan, Enrico (PARTECIPAZIONE E CONFLITTO, 2017)
This article proposes an alternative categorization of the populist phenomena, by elaborating the distinction between electoral-delegative and participative-mobilising populisms. All the populist phe-nomena share some common traits, such as a polarising and antagonist discourse dividing the society into a "People" and some "elites" or privileged sectors, their reliance on a strong leadership, a pretension to be majoritarian and to achieve the power at the national level in order to restore the sovereignty of the People. Nonetheless, the strategies for achieving these goals vary according to the specific diagnoses that would correct the perceived deficiencies of the representative democracies in terms of accountabil-ity of the representatives. The populisms closer to the electoral-delegative pole stress the symbolic di-mension of the concept of representation, thus relying on a strong leader able to "truly interpret" the general will of the People. Those closer to the participative-mobilising pole call for an active involvement of the People in the decision-making process in order to effectively control the public institutions, stress-ing the descriptive dimension of the concept of representation and sometimes questioning the theoreti-cal bases sustaining the representative democracy. I provide a brief discussion on four participative-mo-bilising populist experiences, i.e. the MAS-IPSP, the Kirchnerism, the M5S and Podemos, focusing on their internal organizations and relying on an extensive fieldwork (consisting in one hundred in-depth inter-views with country experts and party's representatives at regional and national levels) that I conducted for a broader research project.